1982
DOI: 10.1128/mcb.2.6.638
|View full text |Cite
|
Sign up to set email alerts
|

Role of Methylation in the Induced and Spontaneous Expression of the Avian Endogenous Virusev-1: DNA Structure and Gene Products

Abstract: The endogenous avian provirus ev-1 is widespread in white leghorn chickens. Although it has no major structural defects, ev-1 has not been associated with any phenotype and is ordinarily expressed at a very low level. In this report, we describe a chicken embryo (Number 1836) cell culture containing both ev-1 and ev-6 which spontaneously expressed the ev-1 provirus. This culture released a high level of noninfectious virions containing a full complement of virion structural (gag) proteins but devoid of reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…It has been suggested that alterations in DNA methylation might provide a means of controlling gene expression (Razin & Riggs, 1980). Consistent with this idea, an inverse relationship has been observed between the level of proviral DNA methylation and virus expression (Niwa & Sugahara, 1981 ;Groudine et al, 1981 ;Conklin et al, 1982). It should be noted, however, that studies of the oestrogen responsive chicken gene vitellogenin have suggested that oestrogen treatment results in a specific demethylation even in a tissue which does not express the vitellogenin gene (Wilks et al, 1982).…”
Section: Discussionsupporting
confidence: 52%
“…It has been suggested that alterations in DNA methylation might provide a means of controlling gene expression (Razin & Riggs, 1980). Consistent with this idea, an inverse relationship has been observed between the level of proviral DNA methylation and virus expression (Niwa & Sugahara, 1981 ;Groudine et al, 1981 ;Conklin et al, 1982). It should be noted, however, that studies of the oestrogen responsive chicken gene vitellogenin have suggested that oestrogen treatment results in a specific demethylation even in a tissue which does not express the vitellogenin gene (Wilks et al, 1982).…”
Section: Discussionsupporting
confidence: 52%
“…AC is also capable of reactivating silent genes on the inactive X chromosome (13,29), which is known to be hypermethylated at the glucose 6-phosphate dehydrogenase and hypoxanthine guanine phosphoribosyl transferase loci (45,48,50). It also activates latent retroviruses, and these events have also been shown to be associated with the loss of 5-methylcytosine (5mC) (5,14,31). All these results support the hypothesis that hypermethylation of DNA sequences can shut off transcription and that AC reactivates genes by demethylating these sequences.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we previously reported that ev-1 is highly methylated, while ev-3 is not (8,18,19). In addition, both ev-1 and ev-2 are inducible with the methylation inhibitor 5-azacytidine (19; unpublished data), indicating that methylation plays a role in at least maintaining provirus repression.…”
Section: Discussionmentioning
confidence: 99%